Races of Puccinia graminis on barley, oat, and wheat in Canada in 2013 and 2014. Issue 1 (2nd January 2021) - Fetch, T.; Mitchell Fetch, J.; Zegeye, T.; Xue, A.
Abstract: Stem rust, caused by Puccinia graminis, is a catastrophic disease that has and continues to cause yield losses in barley, oat, and wheat crops worldwide. Use of host resistance genes is the most economic, efficient, and environmentally best method to control the disease. Resistance genes have been incorporated into most commercial cultivars and have been effective, for races in the North American populations of P. graminis . However, new races of stem rust are constantly emerging and therefore it is imperative to monitor the virulence structure in the populations to detect new races with increased virulence. Stem rust samples were collected in 2013 and 2014 in Manitoba, Ontario, Quebec, and Saskatchewan to determine the incidence and severity of stem rust in barley ( Hordeum vulgare ), oat ( Avena sativa ), and wheat ( Triticum aestivum ) fields and to characterize the virulence dynamics in the pathogen populations. No stem rust was found in cultivated wheat, and incidence was at trace (<1%) levels in barley fields and very low (0–5%) levels in oat fields in 2013 and 2014. In wheat trap plots and collections from barley, race QFCSC of P. graminis f. sp. tritici was dominant in 2013 (85.9%) and was the only race found in 2014. Races MCCFC, QTHJF, RFCSC, RKQSC, and TMRTF were at low (<5%) levels in 2013. From collections in oat fields and stands of wild barley, nine races of P. graminis f. sp. avenae were found in 2013, with TJS (56.9%) and TJJ (23.5%) the most frequent. In 2014, we found only six races and TJS (74.5%) and TJJ (19.1%) were the most frequent. No new races of stem rust were detected in Canada in 2013 or 2014.